Organisational Baseline Study: Overview Report for Rohal Suong, Cambodia (KHM01) - Eam, Dyna; Sovannara, Khean; Vuthy, Chin; Narun, Khlout; Kimnay, Siea (2015)
This report covers the Organisational Baseline Study (OBS) for the Rohal Suong, a CCAFS climate-smart village in Cambodia. During November 2014 interviews were conducted with five organisations working or collaborating with farmers and/or the community in Rohal Suong village, Eak Phnom district and Battambang province. Rohal Soung is an old village and covered largely by flooded forest before the 1990s, the flooded forest provided high value benefits to environment as well as to local villagers. Flooded forest provided a good habitat and feeds to fish, water births and retails; those fish and wild & water animals were caught by villagers for household consumption. The flooded forests, however, were degraded rapidly as a result of agricultural expansions and high demands of fired wood of flooded tree. The grass lands were also converted to rice field over last 10 years; some parts, however, are kept as forage source for their cattle. This OBS report supplements the quantitative household baseline surveys and the qualitative village baseline studies at the same location. The objectives of the organisational baseline study are to:  Provide indicators to monitor changes in behaviours and practices of locally relevant organisations that have climate change related activities in Battambang over time  Understand the provision of information/services at the local level that informs farmers’ decision making about their livelihood strategies in response to climate change